The Role of Public Relations in Enhancing Parental Involvement: Its Implications for Student Character Development - Nur Amalia; Muhammad Anggung Manumanoso Prasetyo (DIDAKTIKA, 2026)
This study was conducted to determine the role of school public relations in increasing parental involvement in student character development at SMA Negeri 1 Tanah Jambo Aye. This study used qualitative methods with a descriptive survey approach. Data were obtained through online interviews with four teachers involved in public relations activities and communication with parents. The results showed that the school uses various communication media such as WhatsApp groups, parent-teacher meetings, social media, and circulars to build relationships with parents. Parental involvement is evident in their participation in school activities, communication with teachers, and assistance with student learning at home. Collaboration between the school and parents has a positive impact on student character development, such as discipline, responsibility, honesty, and cooperation. Therefore, a good relationship between the school and parents is crucial in supporting the sustainable development of student character.